Transportation Network Connectivity in Nusa Cendana University Campus Environment - Muhammad Husain Hasan; Hamza H. Wulakada; Wasti Julita Ndun (Frontier Advances in Applied Science and Engineering, 2024)
The objectives of this research are, (1) To determine the connectivity index of the transportation network in the Undana campus environment, and (2) To determine and increase the level of efficiency of traffic movements in supporting the accessibility needs of transportation users in the Undana campus environment. campus environment. The method used is a quantitative descriptive method which is used to analyze data by describing or illustrating the data that has been collected as it is. The results of the analysis in this research are, with the beta index value (ϐ) of 1.05 indicates that road network connectivity is not arranged linearly or simply. Meanwhile, the gamma index (y) value of 0.38 indicates that the condition of transportation network connectivity is still low. Therefore, infrastructure planning is proposed as a solution to increase the mobility and connectivity index values. Several traffic engineering management scenarios are proposed based on the results of the analysis, namely widening roads, limiting public transportation, scheduling traffic movement activities, improving the safety of traffic signs, encouraging the use of public transportation by providing temporary stops, and monitoring traffic. engineering management.